2017
DOI: 10.1007/s00402-017-2854-0
|View full text |Cite
|
Sign up to set email alerts
|

3D printing lunate prosthesis for stage IIIc Kienböck’s disease: a case report

Abstract: Stage IIIc Kienböck’s disease is a clinical challenge to treat collapse of the lunate bone. A new reconstructive surgery was described in one patient using 3D printing lunate prosthesis. The prosthesis shape was designed by tomographic image processing and segmentation using technology compared with the intact side matched by mirror symmetry and 3D post-processing technologies. The patient recovered nearly full range of motion of the wrist after 12 months. The visual analog scale scores and Cooney scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Inspired by the recent success in treating stage IIIc Kienböck's disease with a 3D printed lunar prosthesis[ 18 ], our team successfully used 3D printing to generate a personalized talus prosthesis with biological function replacement technology to treat seven patients with severe talus collapse and necrosis. Moreover, the tumor in this case is too large to be treated using conventional treatment; therefore, we attempted to treat this case by 3D printing technology to completely solve the problem of easy recurrence of giant cell tumor of bone and restore the patient's walking function close to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the recent success in treating stage IIIc Kienböck's disease with a 3D printed lunar prosthesis[ 18 ], our team successfully used 3D printing to generate a personalized talus prosthesis with biological function replacement technology to treat seven patients with severe talus collapse and necrosis. Moreover, the tumor in this case is too large to be treated using conventional treatment; therefore, we attempted to treat this case by 3D printing technology to completely solve the problem of easy recurrence of giant cell tumor of bone and restore the patient's walking function close to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al reported a case of patient-specific replacement of a collapsed lunate in stage IIIc Kienböck's disease. The implantation of a customized 3D-printed polyethylene spacer led to a nearly full range of motion and good pain relief 12 months after surgery [ 47 ]. The senior author of this article developed and showed the feasibility of a scaphoid prosthesis 3D-printed of titanium and ceramic and suggested 3D-printed Polyetheretherketon (PEEK) for further use [ 48 , 49 ].…”
Section: Practical Applications In Hand Surgerymentioning
confidence: 99%
“…Betrachtet man auch das restliche Skelett der Hand, bietet sich der komplette Knochenersatz wie im ersten obengenannten Beispiel an, jedoch ist es mit der reinen Substitution nicht getan, da vor allem auch die Funktion rekonstruiert werden muss. Kollegen aus China zeigten anhand eines Falles den erfolgreichen Einsatz eines patientenspezifischen Platzhalters bei einem kollabierten Mondbein aufgrund einer Lunatumnekrose [38].…”
Section: Zukunftunclassified